A Review of the Biology, Ecology, and Management of the South American Locust, Schistocerca cancellata (Serville, 1838), and Future Prospects - Trumper, Eduardo Victor; Cease, Arianne J.; Cigliano, María Marta; Copa Bazán, Fernando; Lange, Carlos E.; Medina, Héctor E.; Overson, Rick P.; Therville, Clara; Pocco, Martina E.; Piou, Cyril; Zagaglia, Gustavo; Hunter, David (MDPI, 2022)
In the first half of the twentieth century, the South American Locust (SAL), Schistocerca cancellata (Serville, 1838), was a major pest of agriculture in Argentina, Bolivia, Paraguay, Uruguay, and Brazil. From 1954–2014, a preventive management program appeared to limit SAL populations, with only small- to moderate-scale treatments required, limited to outbreak areas in northwest Argentina. However, the lack of major locust outbreaks led to a gradual reduction in resources, and in 2015, the sudden appearance of swarms marked the beginning of a substantial upsurge, with many swarms reported initially in Argentina in 2015, followed by expansion into neighboring countries over the next few years. The upsurge required a rapid allocation of resources for management of SAL and a detailed examination of the improvements needed for the successful management of this species. This paper provides a review of SAL biology, management history, and perspectives on navigating a plague period after a 60-year recession.